Pengaruh Pengalaman Auditor, Due Profesional Care dan Etika Profesi Terhadap Kualitas Audit - Hanna Hutapea; Rolyana Ferinia (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2022)
This study aims to examine and obtain empirical evidence of the effect of auditor work experience, due profesional care and auditor professional ethics on audit quality at Public Accounting Firms in the South Jakarta area. This research uses a quantitative approach. Data collection is done by distributing questionnaires through google form. The total sample in this study was 70 respondents. By using purposive sampling method. The data analysis technique used is multiple linear regression analysis using SPSS version 25. Based on the results of this study indicate that auditor's work experience, due profesional care and professional ethics of auditors have a positive and significant effect on audit quality.